WEAKLY POSITIVE RH FACTOR, DIAGNOSED FOR THE FIRST TIME IN A WOMAN DURING PREGNANCY (CLINICAL CASE) - Фролова, Юлия Сергеевна; Грищенко, Екатерина Владимировна; Елгина, Светлана Ивановна; Рудаева, Елена Владимировна; Мозес, Кира Борисовна (Mother and Baby in Kuzbass, 2024)
The weakly positive Rh factor (Du phenotype) was described by physician and researcher Frederick Stratton in 1946 as a new variant of the antigen that reacts weakly with anti-D identifying sera. It is characterized by quantitative rather than qualitative differences, unlike the partial variant: with this type of Rh affiliation, the number of antigens on the erythrocyte is reduced. In most cases, this is due to genetic reasons. About 1 % of people have a weakly positive variant of the antigen D of the Rh factor – D weak, aka, «Du». More recently, such a phenotype was defined as negative. With conventional methods for determining Rh affiliation, it was previously difficult to identify a «weak» antigen. But with the use of new immunogenetic methods, it is not difficult to determine the presence of «weakly positive» Rh.The presented article describes a clinical case of pregnancy and childbirth in a woman with a weakly positive Rh factor.
Keywords: pregnancy; childbirth; weakly positive Rh factor